Один день из жизни украинского социума (по результатам применения методики исследования повседневных событий, предложенной Н.В.Паниной) - Середа, В. (Социология: теория, методы, маркетинг, 2008)
Everyday life theories constitute theoretical background of the article. In particular, the author discusses practices of every day life together with sociology of leisure and time budget approaches. The paper is based on Natalia Panina’s pioneering methodology for researching one day in the country’s life. The methodology is based on the open-ended question: “What events of the previous day do you remember most of all?” followed by two closed questions about respondents’ attitude to that day and conflicts happened at that time. The article examines a connection between respondents’ preferred activities, which they described in their recollections of the previous day, and their social-demographic characteristics. As the analysis reveals, strong differences between age, gender and in some cases between places of residence (regions) can be detected.